Islamic Apologetics and Social Construction: Framing Bang Zuma's YouTube Content via James Thrower - Mukhroman, Iman; Halim, Ilim Abdul (UIN Sunan Gunung Djati Bandung, 2025)
Social media has emerged as a critical arena for religious discourse, reshaping the dynamics of Islamic apologetics in contemporary Indonesia. This study aims to analyze the framing strategies employed in the digital content of Bang Zuma, a popular Muslim apologist on YouTube, particularly known for his polemical videos on Islam-Christianity debates. Drawing upon Robert Entman's framing theory and James Thrower's perspective on the social construction of religion, this research investigates how Bang Zuma’s content contributes to the reconstruction of Islamic identity and discourse within digital spaces. Using qualitative content analysis on three viral video transcripts, the study identifies four key framing strategies: (1) constructing a binary between the